Compréhension à la lecture et expression écrite en langue étrangère dans l'enseignement secondaire - Christiane Blondin; Christelle Goffin; Ariane Baye (Recherches en didactique des langues et des cultures)
The European Survey on Language Competences or ESLC collected data on students' foreign language competences and learning environments in 16 European education systems. This study is based on the Common European Framework of Reference for Languages (CEFRL): it assesses the percentage of students who reach the different levels of the CEFR. The target population consists of students from one grade of secondary education who study the target language for at least one full school year. The paper presents the results of the study with regard to reading comprehension and writing in German, English and French. The responses of the teachers to a questionnaire make it possible to describe some of their practices, which differ according to the language concerned, just like their links with the performances of the students.